CERVICAL CYTOLOGIC AND COLPOSCOPIC CHANGES IN CASES USING IUDs FOR A LONG TIME - Yılda Arzu Aba; Mehtap Şentürk; Serkan Kumbasar; Elif Sumer; Özlem Dülge; BulatAytek Şık (International Journal of Health Services Research and Policy, 2017)
The present study aims to examine cervical cytologic and colposcopic changes in patients using IUDs for a long time. Our study is a cross-sectional study that enrolled 188 cases. 62 monogamous patients without a history of sexually transmitted infection, and using an IUD for 5 years or more were included in the study group (Group 1). 126 patients without a previous anamnesis of IUD use and patients in whom IUDs were not detected during the examination were enrolled in the control group (Group 2). All patients underwent a colposcopic examination and a smear was obtained. Patients with a history of HPV were excluded from the study. Smear test results and findings of colposcopic examination of the study and control groups were compared. Gravida, Parity, Number of Births, age at first coitus were determined through the patients’ histories. The mean age of the patients in Group 1 was 38.67, age at first coitus was 19.49, and the mean age in Group 2 was 39.11 and age at first coitus was 18.95 years. There was a significant difference detected in the comparison of Gravida (p=0.03), while parity and NSD parameters were not found significantly different (p=0.15, p=0.14). Rates of mild ectopy in Group 1 and Group 2 were 25.8% and 19.18%, moderate ectopy were 25.8%, 28.6%, severe ectopy were 11.3% and 23.8%, respectively. Polyp detection rate was found 16.7% in Group 1, while it was 40.9% in Group 2. On the other hand, leukoplakia detection rate was 8.3% in Group 1, while it was found 18.2% in Group 2. no statistically significant difference was detected between the two groups. F. Mosaic rate in patients using IUDs was found significantly lower (χ²= 3.74 p= 0.05). As a result of our study, no significant difference could be shown in NTZ, ATZ, Asetowhite, C.Mosaic, F.Punction, C.Punction, Atypical Vascularization, and Schiller rates.